Heavy Metals Tolerance and Biosorption Potential of White Rot Fungi - ASIF HANIF, MUHAMMAD; NAWAZ BHATTI*, HAQ; ASIF ALI†, MUHAMMAD; ASGHER, MUHAMMAD; AHMAD BHATTI, IJAZ (Asian Journal of Chemistry, 2009)
Potentiometeric sorption experiments were conducted for screening of cost-effective 11 strains of white rot fungi isolated from metal contaminated soils of Pakistan. In potentiometeric experiments, it was found that the uptake of the meta l ions by the different strains was accompanied with proton release, indicating that the metal binding occurs via an ion exchange as well as by electrostatic interaction between functional groups and heavy metal ions. The minimum inhibitory concentrations (MIC) suggested that the metal toxicity was dependent on fungal isolates. All white rot fungi showed highest toxicity to Pb(II), Cr(III) and Cr(VI), whereas, Cu(II) and Zn(II) were found to be least toxic heavy metals. Ganoderma lucidum, Agaricus bitorquis (J77)and Pleutrotus sajor-caju were more resistant to all heavy metals in comparison to other fugal isolates. The heavy metal sequestration ability of white rot fungi was also studied. Furthermore, conductometeric titrations were carried out for evaluation of ionizable functional groups. The results of the present study clearly demonstrates that different strains of white rot fungi may have a potential for use as high-value biosorbent of heavy metals and it deserves further investigations for practical applications.